Can solvent induced surface modifications applied to screen-printed platforms enhance their electroanalytical performance?. Issue 9 (11th April 2016) - Blanco, Elias; Foster, Christopher W.; Cumba, Loanda R.; do Carmo, Devaney R.; Banks, Craig E.
Abstract : In this paper the effect of solvent induced chemical surface enhancements upon graphitic screen-printed electrodes (SPEs) are critically benchmarked. Abstract : In this paper the effect of solvent induced chemical surface enhancements upon graphitic screen-printed electrodes (SPEs) is explored. Previous literature has indicated that treating the working electrode of a SPE with the solvent N, N -dimethylformamide (DMF) offers improvements within the electroanalytical response, resulting in a 57-fold increment in the electrode surface area compared to their unmodified counterparts. The protocol involves two steps: (i) the SPE is placed into DMF for a selected time, and (ii) it is cured in an oven at a selected time and temperature. Beneficial electroanalytical outputs are reported to be due to the increased surface area attributed to the binder within the bulk surface of the SPEs dissolving out during the immersion step (step i). We revisit this exciting concept and explore these solvent induced chemical surface enhancements using edge- and basal-plane like SPEs and a new bespoke SPE, utilising the solvent DMF and explore, in detail, the parameters utilised in steps (i) and (ii). The electrochemical performance following steps (i) and (ii) is evaluated using the outer-sphere redox probe hexaammineruthenium(iii ) chloride/0.1 M KCl, where it is found that the largest improvement is obtained using DMF with an immersion time of 10 minutes and a curing time of 30 minutes at 100 °C. Solvent induced chemical surface enhancement upon the electrochemical performance of SPEs is also benchmarked in terms of their electroanalytical sensing of NADH (dihydronicotinamide adenine dinucleotide reduced form) and capsaicin both of which are compared to their unmodified SPE counterparts. In both cases, it is apparent that a marginal improvement in the electroanalytical sensitivity ( i.e. gradient of calibration plots) of 1.08-fold and 1.38-fold are found respectively. Returning to the original exciting concept, interestingly it was found that when a poor experimental technique was employed, only then significant increases within the working electrode area are evident. In this case, the insulating layer that defines the working electrode surface, which was not protected from the solvent (step (i)) creates cracks within the insulating layer exposing the underlying carbon connections and thus increasing the electrode area by an unknown quantity. We infer that the origin of the response reported within the literature, where an extreme increase in the electrochemical surface area (57-fold) was reported, is unlikely to be solely due to the binder dissolving but rather poor experimental control over step (i).